The surgical patient of yesterday, today, and tomorrow: a time-trend analysis based on a cohort of 8.7 million surgical patients - Knoedler, Samuel; Matar, Dany Y.; Friedrich, Sarah; Knoedler, Leonard; Haug, Valentin; Hundeshagen, Gabriel; Kauke-Navarro, Martin; Kneser, Ulrich; Pomahac, Bohdan; Orgill, Dennis P.; Panayi, Adriana C. (International journal of surgery, 2023)
Background: Global healthcare delivery is challenged by the aging population and the increase in obesity and type 2 diabetes. The extent to which such trends affect the cohort of patients the authors surgically operate on remains to be elucidated. Comprising of 8.7 million surgical patients, the American College of Surgeons (ACS) National Surgical Quality Improvement Program (NSQIP) database can be analyzed to investigate the echo of general population dynamics and forecast future trends. - Material and methods: The authors reviewed the ACS-NSQIP database (2008-2020) in its entirety, extracting patient age, BMI, and diabetes prevalence. Based on these data, the authors forecasted future trends up to 2030 using a drift model. - Results: During the review period, median age increased by 3 years, and median BMI by 0.9 kg/m2. The proportion of patients with overweight, obesity class I, and class II rates increased. The prevalence of diabetes rose between 2008 (14.9%) and 2020 (15.3%). The authors forecast the median age in 2030 to reach 61.5 years and median BMI to climb to 29.8 kg/m2. Concerningly, in 2030, eight of ten surgical patients are projected to have a BMI above normal. Diabetes prevalence is projected to rise to 15.6% over the next decade. - Conclusion: General population trends echo in the field of surgery, with the surgical cohort aging at an alarmingly rapid rate and increasingly suffering from obesity and diabetes. These trends show no sign of abating without dedicated efforts and call for urgent measures and fundamental re-structuring for improved future surgical care.
Gesehen am 20.02.2024